Improving tennis player performance using system development interpretations methodology. (1st January 2014) - Shvorin, Dotan; Taaffe, Kevin
This research demonstrates a unique analytical approach to improving a player's performance in the game of tennis. We introduce a system development interpretations (SDI) methodology for associating player characteristics and factors in a hierarchical structure. We then show how this tool is applied in a human performance environment such as tennis. This approach was developed as a multi-disciplinary quality tool for process improvement that identifies factor dependencies and depicts their impact on the resulting player performance. From the implementation of the SDI methodology, the research was able to define the tennis player's difficulties and it has allowed the researchers to build an entire team profile of the Clemson University tennis programme as well as to introduce important conceptual foundations in this field.